Construction of Ag-modified TiO2/ZnO heterojunction nanotree arrays with superior photocatalytic and photoelectrochemical properties. Issue 57 (18th September 2020) - Xu, Kang; Liu, Zhu; Qi, Shihan; Yin, Zhuangzhuang; Deng, Shangkun; Zhang, Miao; Sun, Zhaoqi
Abstract : The work involves the preparation of TiO2 /ZnO heterojunction nanotree arrays by a three-step: hydrothermal, sol–gel, and secondary hydrothermal method, and then modification of Ag quantum dots (QDs). Abstract : The work involves the preparation of TiO2 /ZnO heterojunction nanotree arrays by a three-step: hydrothermal, sol–gel, and secondary hydrothermal method, and then modification of Ag quantum dots (QDs). In the above process, the ZnO nanoparticles attached to the TiO2 surface were subjected to secondary growth by a hydrothermal method to form a unique nanotree structure with TiO2, followed by Ag quantum dot modification by quantum dot deposition. In summary, TiO2 /ZnO nanotree arrays are cited for the first time. The prepared Ag-modified TiO2 /ZnO heterojunction nanotree arrays were found to exhibit enhanced photoelectrochemical and photocatalytic properties. The photocurrent of the Ag-modified TiO2 /ZnO heterojunction nanotree arrays is increased by 8-fold compared to the pure TiO2 nanorod arrays, the photocatalytic degradation rate within 180 minutes increased from 37% to 77% and the kinetic rate constants for the degradation of methyl orange were three times higher than the pure TiO2 nanorod arrays. The improved performance is partly due to the introduction of the TiO2 /ZnO heterojunction nanotree arrays which provide Ag QDs with greater adhesion area. Localized surface plasmon resonance (LSPR) leads to an increase in the intensity of absorbed light due to the modification of Ag QDs. On the other hand the generation of the TiO2 /ZnO heterojunction decreases the forbidden band width, resulting in the redshift of the light absorption edge. Therefore, TiO2 /ZnO heterojunction nanotree arrays are expected to play an important role in solar cells and photocatalytic materials.